Usability Analysis of Augmented Reality-Based Flipbooks as Learning Media for Elementary School Students - Nabila, Aditia Ayu Rahma; Rusdi, Ahmad; As, Zuleriwati; Gultom, Velano Esbi Parsaoran (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Digital transformation in education has driven the adoption of technologies to enhance student engagement and understanding. Augmented Reality (AR) is one such rapidly growing technology, offering immersive and visual learning experiences through 3D objects. When combined with digital flipbooks, AR creates flexiblity, particularly suitable for elementary students. AR flipbooks are seen as promising tools, blending interactive visuals with the familiar digital book. However, their effectiveness must be evaluated from the user’s perspective, especially students as end-users. This study aims to assess the usability of AR flipbooks using the USE instrument (Usefulness, Ease of Use, Ease of Learning, Satisfaction). A descriptive quantitative method was applied to 13 students from SDN 10 Tanjungpinang Kota. The results revealed that usefulness and ease of learning significantly influenced student satisfaction. These findings suggest that the more beneficial and easy-to-understand the media is perceived by students, the higher their satisfaction in using AR flipbook learning tools.